Chemical Biology Applied to the Study of Bacterial Pathogens - Anthouard, Rebecca (Infect Immun, 2015)
In recent years, chemical biology and chemical genomics have been increasingly applied to the field of microbiology to uncover new potential therapeutics as well as to probe virulence mechanisms in pathogens. The approach offers some clear advantages, as identified compounds (i) can serve as a proof of principle for the applicability of drugs to specific targets; (ii) can serve as conditional effectors to explore the function of their targets in vitro and in vivo; (iii) can be used to modulate gene expression in otherwise genetically intractable organisms; and (iv) can be tailored to a narrow or broad range of bacteria. This review highlights recent examples from the literature to illustrate how the use of small molecules has advanced discovery of novel potential treatments and has been applied to explore biological mechanisms underlying pathogenicity. We also use these examples to discuss practical considerations that are key to establishing a screening or discovery program. Finally, we discuss the advantages and challenges of different approaches and the methods that are emerging to address these challenges.